2000
DOI: 10.1590/s1516-35982000000400032
|View full text |Cite
|
Sign up to set email alerts
|

Influência do grão de sorgo como fonte de amido em ovinos alimentados com feno: parâmetros plasmáticos

Abstract: O objetivo deste trabalho experimental foi verificar a influência de diferentes níveis de grão de sorgo, como fonte de amido, nos parâmetros plasmáticos em ovinos alimentados com feno de capim-elefante (Pennisetum purpureum Schum). O sorgo foi utilizado em quatro níveis na dieta: 0, 15, 30 e 45%. Foram usados 12 ovinos machos castrados distribuídos em quatro tratamentos com três repetições. Foram coletadas seis amostras de sangue por animal logo antes da refeição da manhã (hora zero) e 1, 2, 3, 4, 6 e 8 horas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
3
1
0
4
Order By: Relevance
“…Glucose is apparently the specific mediator of nutrition effects on animal reproduction (32) , and it can indicate faults in the homeostatic mechanism that balances glucagon and insulin levels (33) . In this study, we observed glucose levels within the reference range cited for sheep (50-80) (13) , and close to those reported by López e Stumpf Junior (34) , when evaluating the influence of different levels of sorghum grain as an amide source for sheep. The ewes that received diet II showed the best prolificity rates (number of lambs born/number of lambing females) among the three groups of ewes.…”
Section: Discussionsupporting
confidence: 90%
“…Glucose is apparently the specific mediator of nutrition effects on animal reproduction (32) , and it can indicate faults in the homeostatic mechanism that balances glucagon and insulin levels (33) . In this study, we observed glucose levels within the reference range cited for sheep (50-80) (13) , and close to those reported by López e Stumpf Junior (34) , when evaluating the influence of different levels of sorghum grain as an amide source for sheep. The ewes that received diet II showed the best prolificity rates (number of lambs born/number of lambing females) among the three groups of ewes.…”
Section: Discussionsupporting
confidence: 90%
“…Our study helped us obtain a proper response to cause the desired hypoglycemia and hyperinsulinemia. The average values obtained for the analysis of the serum concentrations of insulin and glucose, in our control group, were the same as those found in the veterinary literature 24,25 using the commercial kit employed in humans.…”
Section: Discussionsupporting
confidence: 62%
“…Neste experimento, as concentrações plasmáticas de glicose foram menores justamente nos tratamentos que resultaram em menores ingestões de CNF. López & Stumpf Jr. (2000), avaliando quatro níveis de sorgo em dietas para ovinos contendo de 38 a 82% de feno, observaram que a concentração de glicose para o nível de 0% de inclusão de sorgo (60,4 mg/dL) foi inferior aos demais tratamentos com 15, 30 e 45% de sorgo (72,3; 81,0; 80,5 mg/dL, respectivamente), indicando que a quantidade de CNF da dieta pode afetar a concentração sérica de glicose.…”
Section: Resultsunclassified